2021
DOI: 10.1002/pssb.202100108
|View full text |Cite
|
Sign up to set email alerts
|

Refrigeration through Barocaloric Effect Using the Spin Crossover Complex {Fe[H2B(pz)2]2(bipy)}

Abstract: Spin crossover complexes have a very striking signature of a huge volume change coupled with low–high spin conversion around a critical temperature, which can be pressure tuned in a large temperature interval. Herein, the barocaloric effect is reported in the spin crossover complex {Fe[H2B(pz)2]2(bipy)} (bipy = 2,2′‐bipyridine) from theoretical and applied points of view. The experimental data reveal a giant barocaloric effect, through the isothermal entropy change (ΔST = 83 J kg−1 K−1) around T = 273 K, upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The values of ∆S BCE and ∆T AD are presented in table 2 without taking into account the temperature hysteresis. However, the actual reversible changes in the extensive and intensive BCE, which must be determined in accordance with (7) and (8), significantly depend, albeit to a different extent, on the value of δT 0 (figure 6(b)). Obviously, this effect is critical for materials with δT 0 ≫ 1 K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of ∆S BCE and ∆T AD are presented in table 2 without taking into account the temperature hysteresis. However, the actual reversible changes in the extensive and intensive BCE, which must be determined in accordance with (7) and (8), significantly depend, albeit to a different extent, on the value of δT 0 (figure 6(b)). Obviously, this effect is critical for materials with δT 0 ≫ 1 K.…”
Section: Discussionmentioning
confidence: 99%
“…This point reveals that, firstly, BCE can be realized in solids of different physical origin and, secondly, their largest values can be realized in the region of phase transitions, where the derivative (∂V/∂T) p demonstrates anomalous behavior. Such universality has recently stimulated a significant increase in interest in BCE in inorganic (ferroelastics, ferroelectrics, ferromagnets, superionic conductors, etc), organic (plastic crystals) and organic-inorganic hybrid (two-dimensional metal-halide perovskites, formamidinium iodide, etc) materials [7][8][9][10][11][12][13][14][15]. Until now, despite a lot of publications, intensive study of BCE is mainly aimed at searching for materials demonstrating 'a huge' ('unusual large', 'giant', 'colossal') extensive BCE and undergoing, as a rule, one phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have started exploring other alternative barocaloric materials with suitable refrigeration temperatures. For instance, P. J. von Ranke [23] discovered a giant barocaloric effect in Fe[H 2 B(pz) 2 ] 2 (bipy), with an entropy change (ΔS T = 83 J kg −1 K −1 ) at 273 K. Li et al [24] found a barocaloric effect in a ortho-carborance (C 2 B 10 H 12 ), with an entropy change of ≈86 J kg −1 K −1 at 275 K, and reported NH 4 I [25] as another potential barocaloric material with an entropy change of 71 J kg −1 K −1 at 268 K. However, while these materials have suitable refrigeration temperatures, their entropy change is significantly lower than that of NPG, resulting in a lower refrigeration capacity. Hence, finding a material with both a suitable refrigeration temperature and a colossal barocaloric effect remains a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of such materials have been studied recently and exhibit giant or colossal (or supergiant) BC effects, such as plastic crystals, 6–8 elastomeric polymers (elastomers), 9–13 organic–inorganic hybrid perovskites and metal–organic frameworks 14–17 and other coordination compounds. 18–20 Most of the BC materials studied so far present a more pronounced BC effect only around solid–solid phase transitions, while elastomers present a giant BC effect in wider temperature ranges, even in the absence of phase transitions. 9–13 Nevertheless, solid–liquid phase transitions may significantly increase the BC effects, and, consequently, the potential for application in BC-based refrigerators.…”
Section: Introductionmentioning
confidence: 99%